Психологічні механізми взаємозв’язку тайм-менеджменту та стрес-менеджменту в академічній діяльності студентів: інтегративний підхід до підвищення ефективності навчання - Заіка, П. В. (ХНУРЕ, 2025)
The changes in the educational learning space that have occurred in recent years pose significant challenges for modern student youth. Life and studying during wartime lead to increased stress. To maintain mental health and improve learning effectiveness, it's important to master self-regulation methods, among which stress management and time management play a leading role. The integration of stress and time management methods is an important strategy for improving student performance. The combined application of these methods allows for creating an individual system of time and stress management that takes into account the personal characteristics and needs of the student.
Keywords: тайм-менеджмент; стрес-менеджмент; підвищення ефективності навчання